Effect of Qingjin Huatan decoction on pulmonary function and inflammatory mediators in stable chronic obstructive pulmonary disease: A systematic review and meta-analysis - Xuqin Du; Yan Li; Jiansen Wang; Youqin Jiang; Yaji Liu; Dingrong Zhang; Qi Wu; Shouhong Long (PLoS ONE, 2025)
Background The inflammatory response is the main pathophysiological basis of stable chronic obstructive pulmonary disease (COPD). It is a key factor that leads to frequent exacerbations and disease progression. Suppressing the inflammatory response can improve pulmonary function, prognosis, and quality of life in stable COPD patients. Objective To evaluate the effect of Qingjin Huatan decoction (QJHTD) on pulmonary function and inflammatory mediators in stable COPD patients. Methods Randomized controlled trials (RCTs) on the treatment of stable COPD with QJHTD were retrieved from nine Chinese and English electronic databases up to June 30, 2024. The quality of the studies was assessed using the Cochrane Risk of Bias Tool and the modified Jadad scale. Statistical analysis, sensitivity analysis, and publication bias assessment were performed using Stata 17.0 software. Results A total of 16 RCTs involving 1,228 stable COPD patients were included. Compared to standard treatment, QJHTD significantly improved pulmonary function, with increases in FEV1 (MD = 0.32, 95% CI [0.25, 0.38], p = 0.000), FVC (MD = 0.30, 95% CI [0.22, 0.37], p = 0.000), FEV1/FVC (MD = 5.58, 95% CI [4.81, 6.34], p = 0.000), and PaO2 (MD = 9.62, 95% CI [6.17, 13.08], p = 0.000), and a decrease in PaCO2 (MD = -9.12, 95% CI [–11.96, –6.28], p = 0.000). QJHTD also significantly suppressed the expression of inflammatory mediators, including TNF-α (MD = –7.47, 95% CI [–10.59, –4.34], p = 0.000), IL-6 (MD = -4.33, 95% CI [–6.17, –2.48], p = 0.000), and hs-CRP (MD = –9.11, 95% CI [–11.02, –7.20], p = 0.000). Additionally, QJHTD improved clinical efficacy (RR = 4.60, 95% CI [3.09, 6.86], p = 0.000) without increasing the incidence of adverse reactions (RR = 1.60, 95% CI [0.69, 2.46], p = 0.42). Conclusion The current evidence suggests that QJHTD, as an adjunct therapy to standard treatment, may significantly improve pulmonary function, reduce inflammatory mediators, and enhance clinical efficacy in patients with stable COPD, with a favorable safety profile. However, these findings should be interpreted with caution due to several limitations, including small sample sizes, high heterogeneity among studies, and methodological weaknesses such as lack of blinding. More rigorously designed, high-quality, multicenter trials are needed to confirm these results.